If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -1b = b Solving -5 + -1b = b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -5 + -1b + -1b = b + -1b Combine like terms: -1b + -1b = -2b -5 + -2b = b + -1b Combine like terms: b + -1b = 0 -5 + -2b = 0 Add '5' to each side of the equation. -5 + 5 + -2b = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2b = 0 + 5 -2b = 0 + 5 Combine like terms: 0 + 5 = 5 -2b = 5 Divide each side by '-2'. b = -2.5 Simplifying b = -2.5
| 6-(2x-3)=5-2(x+4) | | 540=h^3+7h^2+12h | | -6n=2.4-12 | | 32+24x+4x^2=96 | | 20-8s=-7(4s-6) | | 3x^2+2.2x+1.21=0 | | 54.15=15.7+3.2x | | 27a^9f^10-18a^7f^8+12a^3f^4= | | 6x-4+2=3x+5 | | x^2-45=19x+21 | | 8y*2-12y+4=y+10 | | 4m-7=m+2 | | Y=4800(1+5)t | | 8x-6=x | | 1+1234567890= | | (2r+1)(8r+5)=0 | | 4(3x+x)+7-5x=8+(-5) | | -94=4m | | -3-7(1)=10x | | w/11 | | 31+3x=-5x+-25 | | M+3.4=7.9 | | 27m^3+8n^6= | | 1/2×-20 | | 24e^7/18e^2x | | 0+7y=-14 | | 3x^2+8x-61=0 | | 6c+14=4+4 | | 3x-4=2x-2-(2-x) | | -8+5y=-13 | | 60/0.75 | | 16(t-5)+5t=7(3t+3)-12 |